Ob osnovnom značenii perfekta v starovavilonskich pis'mach (v svjazi s akkadskimi «epistoljarnymi» glagol'nymi formami) - Kaplan, G.Ch. (Gs Vinogradov)
engl. Resümee: On the Main Meaning of the Perfect in Old Babylonian Letters (in connection with the «epistolary» verbal forms of Akkadian)